Peran Pemerintah Daerah Dalam Penyiaran Di Kawasan Perbatasan (Studi Terhadap Penyelenggaraan Penyiaran di Provinsi Kepri) - Taufiqqurrachman Taufiqqurrachman (Jurnal Selat, 2015)
Basically, broadcasting carries a noble mission that is the fulfillment of human rights in the information field. because as the mass media, broadcasting is able to disseminate information to the public. On the other hand, broadcasters also carry the interests of nation and state. At this point, based on the perspective of media development, it is required a system that can create a partnership between the government and the broadcasting. This article tries to present a juridical studies on the role of Kepriprovincial government toward broadcasting in border area. This article found that broadcasting in border areas Kepri faced with major challenges, namely the limited quality of community resources. but broadcasters have not been able to provide solutions significantly. This is caused by several things, namely broadcasting industry growth imbalances that have triggered the information gap. At the same time communities living in this border region are exposed by broadcasts of foreign broadcasters that are free to air. As a result, national identity crisis that hit society has reached the stage of concern. In accordance with the principle of autonomy, the local government has a position as a regulator and facilitator so that it can play a strategic role to address these issues. As a facilitator, Kepri provincial government has established a local public broadcasters. But due to the limitations of its coverage, the broadcasters have not been able to deliver the expected solution to the problem of information gap and the crisis of national identity. Keywords: Broadcasting in Border Regions, System / Broadcasting Policy